Comparison of posterior trans-intervertebral osteotomy and pedicle Subtraction osteotomy for the correction of thoracolumbar kyphotic deformity secondary to ankylosing spondylitis - Lijin Zhou; Honghao Yang; Jie Wang; Yiqi Zhang; Yunsheng Wang; Yong Hai (Journal of Orthopaedic Surgery and Research)
Abstract Background Ankylosing spondylitis (AS) often leads to severe thoracolumbar kyphotic deformity, requiring surgical correction. Pedicle subtraction osteotomy (PSO) is the gold standard but carries risks of significant blood loss and neurological complications. Posterior trans-intervertebral osteotomy (PTIO) has emerged as a less invasive alternative, but its comparative efficacy and safety remain unclear. This study aimed to compare radiographic outcomes, surgical parameters, and complications between PTIO and PSO in AS-related kyphosis. Methods A single-center retrospective cohort study included 45 AS patients with thoracolumbar kyphosis (19 PTIO, 26 PSO) who underwent posterior spinal correction. Radiographic parameters (global kyphosis GK, sagittal vertical axis SVA, etc.), surgical data (operative time, blood loss), health-related quality of life (SRS-22), and complications were analyzed. Statistical comparisons were performed using independent t-tests or Mann-Whitney U tests for continuous variables and chi-square/Fisher’s tests for categorical variables. Results Both groups achieved significant kyphosis correction, with no differences in postoperative GK (PTIO: 51.4° ± 13.3° vs. PSO: 47.4° ± 13.0°, P > 0.05) or SVA (PTIO: 59.1 ± 50.3 mm vs. PSO: 49.0 ± 47.1 mm, P > 0.05). PTIO showed lower intraoperative blood loss (600.9 ± 264.6 mL vs. 1088.7 ± 287.9 mL, P = 0.009) and fewer neurological complications (5.3% vs. 15.4%, P = 0.003). Health-related quality of life improved similarly in both groups (P > 0.05). Conclusion PTIO provides comparable radiographic correction to PSO while reducing blood loss and neurological risks. It represents a viable, less invasive alternative for AS-related kyphosis, particularly when anterior column support is achievable. Further studies with long-term follow-up are warranted to validate these findings.